Does physical fitness and parenting transformational style predict happiness and wellbeing and distress in adolescents? (¿La condición física y el estilo parental transformacional predicen la felicidad, el bienestar y angustia psicológica de los adolesce - Alberto Ruiz-Ariza; Manuel J. De la Torre-Cruz; Kaija Appelqvist-Schmidlechner; Nina Tamminen; Emilio J. Martínez-López (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Abstract: There is a growing interest on the relationships between family functioning and behaviors that promote physical and psychological well-being in children and adolescents. The aim of the study was to assess the association of parenting transformational style with happiness, wellbeing and distress in adolescents, beyond of physical fitness influence, and independently of age and body mass index. Data were gathered among 868 Spanish schoolchildren aged 12-16 years (M=14.07, SD=1.24) with a self-administered questionnaire and conducting physical fitness tests. The findings showed that age and the perception of a maternal and paternal transformational style predicted happiness, wellbeing and distress in adolescent girls. In boys, only the parental transformational style acted as a significant predictor, independently of fitness level. Muscular strength contributed to explain the wellbeing in adolescent girls independently of transformational style; however, it did not happen in speed-agility and cardiorespiratory capacity. Findings suggest that promotion of parenting transformational style is beneficial to the psychological wellbeing, above all in younger adolescents. In girls, promotion of higher muscular strength could contribute to improve happiness and wellbeing independently of parental transformational styles.